Which proportion of SR investments is enough? A survey-based approach - Gregor Dorfleitner; Mai Nguyen (Business Research, 2016)
Abstract This article examines the determinants of the optimal percentage that private investors seek to invest in a socially responsible (SR) way when forming their portfolio. By conducting a global online survey in English, German and French, we find indications that it is sufficient for the majority of investors to have a certain amount of their budget invested sustainably. Accordingly, the optimal proportion tends to be lower the higher the available investment volume is. In addition, the non-financial utility derived from SR investments appears to be independent of the form of financing the investor provides. Moreover, the results show that well-educated women and slightly younger persons seek to invest a higher percentage of their portfolio socially responsibly.